Improvement of Urinary Stones Analysis Combining Morphological Analysis and Infrared Spectroscopy. (26th April 2018) - Gervasoni, Jacopo; Primiano, Aniello; Ferraro, Pietro Manuel; Urbani, Andrea; Gambaro, Giovanni; Persichilli, Silvia
Abstract : Daudon et al. have developed a complex morphoconstitutional classification of renal stone in six different morphological types and several subtypes. According to this classification, a precise correspondence exists between causes of renal stones and subtypes with a great clinical relevance and can be considering a sort of shortcut for the metabolic diagnosis in renal stone patients. Now the diagnosis of causes of renal stones generally requires repeated biochemical investigations on urine and blood samples and usually remains presumptive. We analyzed 150 urinary stones both by stereoscopic microscopy and Fourier transform infrared spectroscopy. The comparison of 150 stones did not reveal any disagreement. We have only 20 partial agreement, and clinicians agreed that the imprecise information obtained with morphological analysis alone would have missed an important clinical finding only in 3 cases. In conclusion, in our opinion, the analysis of urinary stone must combine two different analytical techniques: morphological analysis by stereomicroscope and biochemical analysis with the FT-IR.